Ultra-high dose rate (FLASH) carbon ion irradiation: dosimetry and first cell experiments - Tinganelli, Walter; Sokol, Olga; Quartieri, Martina; Puspitasari, Anggraeini; Dokić, Ivana; Abdollahi, Amir; Durante, Marco; Haberer, Thomas; Debus, Jürgen; Boscolo, Daria; Voss, Bernd; Brons, Stephan; et al. (International journal of radiation oncology, biology, physics, 2022)
Purpose - To establish a beam monitoring and dosimetry system to enable the FLASH dose rate carbon ion irradiation and investigate, at different oxygen concentrations, the in vitro biological response in comparison to the conventional dose rate. - Methods and Materials - CHO-K1 cell response to irradiation at different dose rates and at different levels of oxygenation was studied using clonogenic assay. The Heidelberg Ion-Beam Therapy Center (HIT) synchrotron, after technical improvements, was adjusted to extract ≥5 × 108 12C ions within approximately 150 milliseconds. The beam monitors were filled with helium. - Results - The FLASH irradiation with beam scanning yields a dose of 7.5 Gy (homogeneity of ±5%) for a 280 MeV/u beam in a volume of at least 8 mm in diameter and a corresponding dose rate of 70 Gy/s (±20%). The dose repetition accuracy is better than 2%, the systematic uncertainty is better than 2%. Clonogenic assay demonstrates a significant FLASH sparing effect which is strongly oxygenation-dependent and mostly pronounced at 0.5% O2 but absent at 0% and 21% O2. - Conclusion - The FLASH dose rates >40 Gy/s were achieved with carbon beams. Cell survival analysis revealed FLASH dose rate sparing in hypoxia (0.5%-4% O2).